2000
DOI: 10.1111/j.1749-6632.2000.tb06384.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Alzheimer's Disease in the Cholesterol‐fed Rabbit, Including Vascular Inflammation: Preliminary Observations

Abstract: We determined the levels of endothelial inflammation using MECA-32 antibody and alpha 4 nicotinic receptor subunit densities employing [3H]epibatidine binding in the brains of Alzheimer's disease (AD) patients, cholesterol-fed rabbits, and appropriate controls. We also assessed rabbit brain for beta-amyloid levels and immunohistochemical localization, and for evidence of blood-brain barrier breach using normally-excluded Evans Blue dye. Dietary cholesterol induced a twofold increase in beta-amyloid concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(124 citation statements)
references
References 26 publications
(58 reference statements)
5
119
0
Order By: Relevance
“…Cholesterol-rich diets suppress clearance of apo E-rich remnant lipoproteins by high-affinity pathways and via heightened inflammatory processes. 49 ) with negative numbers being indicative of an inverse relationship. Probability of a significant correlation is indicated for P values better than 0.05…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol-rich diets suppress clearance of apo E-rich remnant lipoproteins by high-affinity pathways and via heightened inflammatory processes. 49 ) with negative numbers being indicative of an inverse relationship. Probability of a significant correlation is indicated for P values better than 0.05…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cholesterol, which decreases the membrane fluidity [15,35,72,109] there are some molecules that fluidize the membrane. Prominent among them is alcohol (e.g.…”
Section: Membrane Fluiditymentioning
confidence: 99%
“…Employing this approach, we demonstrated that the α5 integrin subunit is expressed specifically by angiogenic endothelial cells within the hypoxic CNS. Two other studies have described re-expression of the MECA-32 antigen on endothelial cells in the adult brain during neuroinflammatory conditions (Engelhardt et al, 1994;Sparks et al, 2000). In one of these, injection of Corynebacterium parvum induced endothelial expression of ICAM-1 and VCAM-1 on all vessels throughout the CNS, but MECA-32 expression on endothelial cells only at the center of the inflammatory infiltrate (Engelhardt et al, 1994).…”
Section: Temporal Expression Pattern Of Fibronectin α5 Integrin and mentioning
confidence: 99%